Evaluation Grain Yield and Yield Component of Three Wheat Cultivars to Drought Stress and Different Levels of Nitrogen - M.R. Enayatgholizadeh; G. Fathi; M. Razaz (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī, 2011)
To study the effect of drought stress and N fertilizer application on biological yield, grain yield and yield component of three wheat cultivars, a field experiment was conducted in 2006-2007 at Shushter region in Iran. The experiment was a factorial based on completely randomized block design with replications. Treatments were wheat cultivars (Chamran, Showa and Falat), N fertilizer in two levels (50 and 150 kg/ha) and levels of drought stress (without stress, and stress at grain filling). Chamran and Falat were soft bread wheat type  and Showa was durum. Results indicated that under drought stress Chamran had the higher grain yield (5584 kg/ha) as compared to Showa (5332 kg/ha) and Falat (4821 kg/ha).The high level of N increased grain yield by 45% against low level N application. Response of Chamran to N fertiliser was more than that of Showa and Falat respectively. Spike number, grain number per spike and 1000 grain weight affected grain yield